Prevalence, consequences, and contributing factors beyond verbal and physical workplace violence against nurses in peripheral hospitals - Alnaeem, Mohammad M.; Hasan Suleiman, Khaled; Alzoubi, Majdi M.; Sumaqa, Yasmeen Abu; Al-Mugheed, Khalid; Saeed Alabdullah, Amany Anwar; Farghaly Abdelaliem, Sally Mohammed (Frontiers in Public Health, 2025)
BackgroundGlobally, nearly one-third of workplace violence (WPV) occurs in the health sector. Exposure to WPV among Jordanian nurses has been widely speculated to be underreported. Understanding of the factors contributing to WPV among nurses and their consequences is limited.ObjectivesThis study aimed to examine the consequences and contributing factors of WPV and explore suggestions for reducing WPV among nurses working in peripheral hospitals.MethodsThis descriptive, cross-sectional study included 431 Jordanian nurses. Data were collected using a self-report instrument between December 2022 and June 2023. A modified version of the ILO/ICN/WHO/PSI Workplace Violence in the Health Sector Country Case Study Questionnaire developed and validated in 2003 was used.ResultsThe ages of the participants ranged from 20 to 49 years. A total of 349 nurses (81%) had experienced verbal violence, while 110 (25.5%) had experienced physical violence. Of the 110 nurses who were physically attacked, 44 (40 %) reported that an investigation was conducted to determine the cause of the incident. Approximately 38.2% of incidents involving physical violence in the last 12 months involved the use of weapons. The current study revealed that 59.6% of the nurses reported that verbal incidents were common in their workplace. The highest level of agreement among all participants was leniency in applying penalties to perpetrators of violence inside hospitals. The majority of participants (95.8%) agreed that improving staff-patient communication skills would effectively reduce violence.ConclusionCreating awareness among healthcare professionals, patients, and the general public regarding the impact of WPV and the importance of respect and professionalism is crucial.